Nkx2‐3 induces autophagy inhibiting proliferation and migration of vascular smooth muscle cells via AMPK/mTOR signaling pathway. Issue 11 (30th April 2021) - Zheng, Huajun; Zhai, Weicheng; Zhong, Chongbin; Hong, Qingqing; Li, Hekai; Rui, Bowen; Zhu, Xingxing; Que, Dongdong; Feng, Liyun; Yu, Bin; Huang, Guanlin; Yin, Jianlong; et al.
Abstract: Vascular remodeling and restenosis are common complications after percutaneous coronary intervention. Excessive proliferation and migration of vascular smooth muscle cells (VSMCs) play important roles in intimal hyperplasia‐induced vascular restenosis. NK2 Homeobox 3 (Nkx2‐3), a critical member of Nkx family, is involved in tissue differentiation and organ development. However, the role of Nkx2‐3 in VSMCs proliferation and migration remains unknown. In this study, we used carotid balloon injury model and platelet‐derived growth factor‐BB (PDGF)‐treated VSMCs as in vivo and in vitro experimental models. EdU assay and CCK‐8 assay were used to detect cell proliferation. Migration was measured by scratch test. Hematoxylin and eosin staining and immunohistochemistry staining were used to evaluate the intimal hyperplasia. The autophagy level was detected by fluorescent mRFP‐GFP‐LC3 in vitro and by transmission electron microscopy in vivo. It was shown that Nkx2‐3 was upregulated both in balloon injured carotid arteries and PDGF‐stimulated VSMCs. Adenovirus‐mediated Nkx2‐3 overexpression inhibited intimal hyperplasia after balloon injury, and suppressed VSMCs proliferation and migration induced by PDGF. Conversely, silencing of Nkx2‐3 by small interfering RNA exaggerated proliferation and migration of VSMCs. Furthermore, we found that Nkx2‐3 enhanced autophagy level, while the autophagy inhibitor 3‐MA eliminated the inhibitory effect of Nkx2‐3 on VSMCs proliferation and migration both in vivo and in vitro. Moreover, Nkx2‐3 promoted autophagy in VSMCs by activating the AMP‐activated protein kinase/mammalian target of rapamycin (AMPK/mTOR) signaling pathway. These results demonstrated for the first time that Nkx2‐3 inhibited VSMCs proliferation and migration through AMPK/mTOR‐mediated autophagy. Abstract : First, we found that Nkx2‐3 inhibited proliferation and migration in PDGF‐BB‐treated VSMCs and balloon‐injured vessels. Second, we verified that Nkx2‐3‐promoted autophagy suppressed proliferation and migration of VSMCs in vivo and in vitro. Finally, we demonstrated that Nkx2‐3 promoted autophagy via AMPK/mTOR signaling pathway.